Pengaruh Panjang dan Diameter Stud terhadap Keruntuhan Geser Struktur Komposit Baja-Beton - Ayu Hapsari, Rahma Nindya; Nurhuda, Ilham; Nuroji, Nuroji (Department of Civil Engineering, Diponegoro University, 2018)
Composite structures of concrete slabs and steel beams require shear connectors to transfer shear force between steel beams and concrete slabs. The strength of stud shear connector specified on SNI 03-1729-2013 only considers the effect of stud diameter, however the length of a stud may influence its behavior and strength. This research observes the effects of length and diameter (?/?) of shear connectors on the strength. This research was conducted using the push out method explain in AS-4347- Part I. The test specimens observed in this research were concrete and steel composites, composing IWF 350x175x11x14 mm and concrete blocks of size 450x225x160 mm. The studs were made of steel reinforcements with diameter (?) of 10, 16 and 22 mm, were welded on IWF with 5 mm weld thickness. The length of studs for each stud diameter were 4d, 5d, and 6d. The results indicate that the increase in stud diameter will increase the load capacity of stud. The length of studs effect its load capacity. A slim stud experiences large bending moment at the base of the shear connector. The results show that the highest value of load capacity is measured at specimens with ?/? ratio of 5.